2022
DOI: 10.20452/pamw.16218
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase (MTHFR) gene c.655C>T and c.1286A>C and SERPINE 1 -675 4G/5G polymorphisms in Polish patients with venous thromboembolism and cryptogenic ischemic stroke

Abstract: Methylenetetrahydrofolate reductase (MTHFR) gene c.655C>T and c.1286A>C and SERPINE 1 -675 4G/5G polymorphisms in Polish patients with venous thromboembolism and cryptogenic ischemic stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…On the other hand, previously published data of similar studies which found that heterozygote genotype for MTHFR C677T was present in (40.0%) while homozygote genotype were present in (7.5%) of studied VTE patients (14)(15)(16) . We found that genotyping frequency of MTHFR C677T polymorphism had no statistically significant difference between VTE subgroups (Chi-Square test (X2) equals 1.156 and P-value equals 0.561), this finding was in agreement with others (17)(18)(19) We found that sixty percent of patients in our study had lower-extremity DVT, whereas twenty-five percent had pulmonary thromboembolism, and fifteen percent had both. Similarly, (26) found that approximately 2/3 of VTE is clinically manifested as DVT, and 1/3 manifests as isolated PE or PE coexisting with DVT.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, previously published data of similar studies which found that heterozygote genotype for MTHFR C677T was present in (40.0%) while homozygote genotype were present in (7.5%) of studied VTE patients (14)(15)(16) . We found that genotyping frequency of MTHFR C677T polymorphism had no statistically significant difference between VTE subgroups (Chi-Square test (X2) equals 1.156 and P-value equals 0.561), this finding was in agreement with others (17)(18)(19) We found that sixty percent of patients in our study had lower-extremity DVT, whereas twenty-five percent had pulmonary thromboembolism, and fifteen percent had both. Similarly, (26) found that approximately 2/3 of VTE is clinically manifested as DVT, and 1/3 manifests as isolated PE or PE coexisting with DVT.…”
Section: Discussionsupporting
confidence: 91%
“…An unprovoked episode of venous thromboembolism (VTE) was defined as previously described [13]. The diagnosis of deep vein thrombosis (DVT) was established on the basis of a positive finding on color duplex sonography [11].…”
Section: Methodsmentioning
confidence: 99%